Kualitas Laporan Keuangan: Implementasi Sistem Informasi Akuntansi Dan Komitmen Organisasi Dimoderasi Pemahaman Akuntansi - Deva Dwi Ifanka; Rida Perwita Sari (Ekonomis: Journal of Economics and Business, 2022)
Problems related to financial reports are still common, this shows the need to improve the quality of financial reports. This study aims to examine the effect of the implementation of accounting information systems and organizational commitment on the quality of financial reports with understanding of accounting as a moderating variable at UPTD Puskesmas in Bojonegoro Regency. The population in this study were all treasurers or financial management employees at 35 UPTD Puskesmas throughout Bojonegoro Regency. The sampling technique used is purposive sampling technique, resulting in a total of 70 employees. The type of data used is primary data with the data collection method using a questionnaire. The data analysis technique used is Partial Least Square (PLS) with the help of WarpPLS 7.0 software. The results showed that the implementation of accounting information systems and organizational commitment had a significant effect on the quality of financial reports. Understanding of accounting is able to moderate the effect of the implementation of accounting information systems and organizational commitment on the quality of financial reports. This study proves that the implementation of accounting information systems and organizational commitment can improve the quality of financial reports both as the main factor and as a supporting factor.